2002
DOI: 10.1097/01.asn.0000025282.48298.7b
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Caffeine on Renal Epithelial Cells from Patients with Autosomal Dominant Polycystic Kidney Disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a hereditary disorder characterized by the progressive enlargement of cysts derived from tubules. Tubule cell proliferation and chloride-dependent fluid accumulation, mechanisms underlying cyst expansion, are accelerated by adenosine 3':5'-cyclic monophosphate (cAMP). This study examined the extent to which caffeine may stimulate the production of cAMP by cyst epithelial cells, thereby adversely increasing proliferation and fluid secretion. Mural epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 33 publications
0
74
0
2
Order By: Relevance
“…96 High caffeine intake may, therefore, be a risk factor for cyst enlargement and ADPKD progression, although a small clinical study has suggested no correlation between mild caffeine intake and TKV by ultrasound. 97 Nevertheless, it is recommended to counsel patients with ADPKD to limit their caffeine intake.…”
Section: Birth Weightmentioning
confidence: 99%
“…96 High caffeine intake may, therefore, be a risk factor for cyst enlargement and ADPKD progression, although a small clinical study has suggested no correlation between mild caffeine intake and TKV by ultrasound. 97 Nevertheless, it is recommended to counsel patients with ADPKD to limit their caffeine intake.…”
Section: Birth Weightmentioning
confidence: 99%
“…The additional water should be free of caffeine (77) and sugar (78) and contain vanishingly low amounts of dichloroacetate (79) and fluoride (80). A reasonable goal is to drink fluids as evenly as possible throughout waking hours and immediately before going to bed.…”
Section: Which Adpkd Patients Can Safely Increase Water Intake and Homentioning
confidence: 99%
“…The faster growth of kidney cysts in male individuals with ADPKD and also earlier ESRD in male individuals with PKD2 suggest that male hormonal factors may be important in renal cystic disease (20,43). Caffeine exposure has been considered a risk factor in PKD, and evidence that caffeine can increase the production of cAMP in cyst-derived cells, which stimulate proliferation and fluid secretion (72), provides some justification for avoiding caffeinecontaining beverages. Smoking has been shown to be a risk factor for more rapid progression in patients with renal disease, including ADPKD, with increased risk for chronic renal failure and ESRD, especially in men (73).…”
Section: Environmental Influencesmentioning
confidence: 99%